2022
DOI: 10.1111/ahe.12798
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphological, histochemical and scanning electron microscopic investigation of the proventriculus (Ventriculus glandularis) of the hooded crow (Corvus cornix)

Abstract: The hooded crow (Corvus cornix) belongs to the order Passeriformes (family Corvidae: genus Corvus, species C. cornix). These species are classified as omnivorous birds that feed on grains, seeds, fruits, insects, reptiles and small birds, and they are distributed in Eastern and Northern Europe, and the Middle East (Hutchins et al., 2002).Anatomically, the avian stomach is composed of two definite compartments: the proventriculus and the ventriculus "gizzard" (Saran & Meshram, 2020). Both parts are morphologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 25 publications
(55 reference statements)
5
7
0
Order By: Relevance
“…The wall of the moorhen proventriculus appeared in the present study containing superficial (mucosal) and deep (submucosal) proventricular glands. A similar presence of these glands has also been reported in the proventriculus of moorhen [ 37 ] and other avian species including the red jungle fowl [ 38 ], turkey [ 39 ] and hooded crow [ 40 ]. Additionally, the present study found that the deep proventricular glands filled a massive part of the proventricular wall, about two-thirds of the total wall thickness, suggesting a strong digestive ability for the studied species.…”
Section: Discussionsupporting
confidence: 75%
“…The wall of the moorhen proventriculus appeared in the present study containing superficial (mucosal) and deep (submucosal) proventricular glands. A similar presence of these glands has also been reported in the proventriculus of moorhen [ 37 ] and other avian species including the red jungle fowl [ 38 ], turkey [ 39 ] and hooded crow [ 40 ]. Additionally, the present study found that the deep proventricular glands filled a massive part of the proventricular wall, about two-thirds of the total wall thickness, suggesting a strong digestive ability for the studied species.…”
Section: Discussionsupporting
confidence: 75%
“…Histology of the WWBT proventriculus wall showed mucosa, submucosa, muscularis, and serosa, as reported in many avian species (Abdel Maksoud et al, 2022; Ahmed et al, 2011; Beheiry, 2018; Eidaroos et al, 2008; El‐Mansi et al, 2021; Ibrahim et al, 2020; Kadhim et al, 2011; Sinha et al, 2018). The submucosa layer is, however, not observed in some birds, such as yellow‐billed grosbeak (Zhu et al, 2013), and black‐tailed crake (Zhu, 2015).…”
Section: Discussionsupporting
confidence: 68%
“…Additionally, Abdel Maksoud et al (2022) in crow, Ahmed et al (2011) in quail, and Kadhim et al (2011) in red jungle fowl, found the apices of the lamina epithelialis notably showed +ve PAS (neutral mucin) and AB reactions (acidic mucin). These reports are consistent with our findings.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations